Planning and analyzing foreign direct investment projects emerging research and opportunities - Sariaslan, Halil (Business Science Reference, 2019)
"This book focuses on foreign direct investment projects that are proposals for making fixed or real capital investments abroad. It deals with how foreign or international direct investment projects should be prepared and designed in detail to determine all business activities involved in and costs associated with investment proposals"--